The dose-response relationship between in-ear occupational noise exposure and hearing loss. Issue 10 (3rd July 2013) - Rabinowitz, Peter M; Galusha, Deron; Dixon-Ernst, Christine; Clougherty, Jane E; Neitzel, Richard L
Abstract : Objectives: Current understanding of the dose-response relationship between occupational noise and hearing loss is based on cross-sectional studies prior to the widespread use of hearing protection, and with limited data regarding noise exposures below 85 dBA. We report on the hearing loss experience of a unique cohort of industrial workers, with daily monitoring of noise inside of hearing protection devices. Methods: At an industrial facility, workers exhibiting accelerated hearing loss were enrolled in a mandatory programme to monitor daily noise exposures inside of hearing protection. We compared these noise measurements (as time-weighted LAVG ) to interval rates of high-frequency hearing loss over a 6-year period using a mixed-effects model, adjusting for potential confounders. Results: Workers' high-frequency hearing levels at study inception averaged more than 40 dB Hearing threshold level (HTL). Most noise exposures were less than 85 dBA (mean LAVG 76 dBA, IQR 74–80 dBA). We found no statistical relationship between LAvg and high-frequency hearing loss (p=0.53). Using a metric for monthly maximum noise exposure did not improve model fit. Conclusions: At-ear noise exposures below 85 dBA did not show an association with risk of high-frequency hearing loss among workers with substantial past noise exposure and hearing loss at baseline. Therefore, effective noise control to below 85 dBA may lead to significant reduction in occupational hearing loss risk in such individuals. Further research is needed on the dose-response relationship of noise and hearing loss in individuals with normal hearing and little prior noise exposure.